The impact of schistosomiasis co-infection in the presentation of viral hepatitis B in migrants: An observational study in non-endemic area. Issue 35 (May 2020) - Marchese, Valentina; Beltrame, Anna; Angheben, Andrea; Marocco, Stefania; Gaeta, Giovanni Battista; Bisoffi, Zeno
Abstract: Background: In Europe, the prevalence rates of schistosomiasis and HBV infection in migrants from sub-Saharan Africa are high. The co-infection schistosomiasis-HBV has been scarcely studied. Methods: This is a retrospective study assessing differences in clinical presentation, laboratory and ultrasound findings in a cohort of migrants admitted at the Department of Infectious - Tropical Diseases and Microbiology IRCCS Sacro Cuore Don Calabria Hospital of Negrar (Northeast Italy) with schistosomiasis, HBV infection or both. Results: Of the 227 migrants, 175 (77.1%) with a diagnosis of schistosomiasis were classified as SCHISTO group, 35 (15.4%) with schistosomiasis and hepatitis B were classified as SCHISTO/HBV group, and 17 (7.5%) patients with a diagnosis of HBV infection were classified as HBV group. S. mansoni was found in 47 patients, classified in MANSONI (38/175, 21.7%) or MANSONI/HBV (9/35, 25.7%) group depending on HBsAg status. Mean transaminases and APRI index values were higher in SCHISTO/HBV compared to SCHISTO group (p < 0.01). AST differed between MANSONI/HBV and MANSONI group (p = 0.038). No differences were found between SCHISTO/HBV and HBV group. Eosinophil count and total IgE differed only between MANSONI/HBV and HBV group (p = 0, 049). Conclusions: Schistosomiasis seems not to increase the liver damage in people with HBV infection. Conversely, finding elevated transaminases in patients with schistosomiasis should alert for presence of HBV.